As faces e as vozes da polêmica - Mariza Gabriela de Lacerda (2023)
Education can be understood as a socialized practice that involves as much the organization of an internal school space as of an external social space. Its understanding also requires considering the presence of a historical, cultural and political continuum that accompanies and guides educational processes over time. For this reason, we consider the Escola Sem Partido [School Without Party] initiative a controversial and sensitive issue because it deals with teaching from the restrictive perspective of ideology, placing it in the midst of social clashes and ruptures while mobilizing dissident subjectivities and sensitivities. In this scenario, we seek, in this thesis, to understand the roles of language in sociocommunicative and intersubjective exchanges directed to the controversial theme in question, investigating the facets and voices of this public controversy. To this end, we adopted qualitative research and interpretative documentary analysis for methodological purposes. In the organization of the corpus, we selected ten opinionated texts in different informative media in order to compile diversified positions present in the public sphere. The theoretical framework of the study is located within the scope of Discourse Analysis and Argumentation Studies, based on an integrated analytical approach to the enunciative and argumentative organization of the polemical discourse. After the description and analysis of the data, we understand that the polemic functions as a sociodiscursive modality by enabling the management of conflicting points of view, illustrating the relevance of dissent in the democratic regime and in public discussions directed to relevant issues for society. Concomitantly, enunciation proved to be conducive to the staging of antagonistic roles and sayings, allowing the attribution of actions, the distribution of processes and the expression of nuances of subjectivity. In turn, argumentation proved to be a necessary way to search for answers and reasons, enabling the mobilization of doxic elements, the emergence of evaluative domains and the functioning of ideology as an argumentative arsenal.Keywords: school without party; polemic; enunciation; argumentation; opinion; informative media.